M. Yaşar Kandemir’in hayatı, eserleri ve çocuğun din eğitimi - Yahşi, Ömer (My University, 2006)
ABSRACT Mehmet Yaşar Kandemir is a man of science and an idealist lecturer with the academic studies, the students he has educated and the works directed towards public in theological sciences, particularly in the field of the study of the prophet Muhammed’s in our country. He contributed to the study of the prophet Muhammed’s to get the place it deserves in our country in the term of Republic with the academic studies he carrried out and the students he educated. As soon as he had realized the need for Religious Education of the public, he turned to the public and their children and began to publish a lot of books in an effort and idealism to to raise their knowledge level. Kandemir, has produced works to each member o the public from the age of seven to seventy. These books are accumulation of his academic knowledge, meticulous studying and literary taste, prepared semi academic serious works. This thesis, which states the religious education of children, is composed of three chapters originating with the children’s books Kandemir wrote. First chapter of the thesis is about Kandemir’s life, mental structure and Works. Second chapter deals with the education and the importance and necessity of religious eduction of children and the essential part of the thesis is chapter three in which Kandemir’s focus of religious education. Initially, I wolud like to express my gratitude to my thesis Mustafa Usta whose intellectual advise helped me to analyze such a topic in the process of my study. I would also like to state my thanks M. Yaşar Kandemir who spent his valuable time in answering my questions. My thanks also go to İ. Lütfi Çakan, Abdülkerim Özaydın, İbrahim Hatiboğlu, and Emin Aşıkkutlu whose vluable thoughts from whom I benefited during the negotiations in my thesis. I am grateful to my wife
Keywords: Din Eğitimi; Kandemir, M. Yaşar, 1939-